Deciphering the Functional Role of RIPK4 in Melanoma - Ewelina Madej (MDPI AG, 2021)
The receptor-interacting protein kinase 4 (RIPK4) plays an important role in the development and maintenance of various tissues including skin, but its role in melanoma has not been reported. Using patient-derived cell lines and clinical samples, we show that RIPK4 is expressed in melanomas at different levels. This heterogenous expression, together with very low level of RIPK4 in melanocytes, indicates that the role of this kinase in melanoma is context-dependent. While the analysis of microarray data has revealed no straightforward correlation between the stage of melanoma progression and RIPK4 expression in vivo, relatively high levels of RIPK4 are in metastatic melanoma cell lines. RIPK4 down-regulation by siRNA resulted in the attenuation of invasive potential as assessed by time-lapse video microscopy, wound-healing and transmigration assays. These effects were accompanied by reduced level of pro-invasive proteins such as MMP9, MMP2, and N-cadherin. Incubation of melanoma cells with phorbol ester (PMA) increased PKC-1β level and hyperphosphorylation of RIPK4 resulting in degradation of RIPK4. Interestingly, incubation of cells with PMA for short and long durations revealed that cell migration is controlled by the NF-κB signaling in a RIPK4-dependent (RIPK4high) or independent (RIPK4low) manner depending on cell origin (distant or lymph node metastasis) or phenotype (mesenchymal or epithelial).